Eksplorasi Unsur Geometri dalam Arsitektur Masjid Agung KH Anas Mahfud sebagai Sumber Belajar Berbasis Etnomatematika - Ridho’i, Mohammad (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
The purpose of this study is to explore the elements of geometry in the architecture of Agung Anas Mahfud and analyze the application of mathematical concepts in geometry as an ethnomathematics-based learning resource. The research approach used is qualitative with ethnographic method, which allows in-depth analysis of the relationship between mosque architectural elements and geometry concepts. Data were collected through field observations and interviews with the Takmir of Anas Mahfud Great Mosque, and supported by the study of relevant literature. The results of this study show that the architecture of Anas Mahfud Great Mosque contains various elements of geometry that can be associated with the concept of mathematics. Various elements of the mosque building have clear geometric shapes, and the utilization of ethnomathematics elements as a geometry teaching model. The geometry elements found are 1). Dome and Roof, 2). Doors, 3). Window, 4). Pillar, 5). Tower, 6). Ventilation, 7. Satire. The geometry concepts found are flat planes and curved side spaces. By integrating ethnomathematics in geometry learning, it is expected that students can understand math concepts better through an approach that is relevant to their environment.